Drought Enhances Nitrogen Uptake and Assimilation in Maize Roots. (1st January 2017) - Wang, Huan; Yang, Zongze; Yu, Yanan; Chen, Siyu; He, Zhang; Wang, Yong; Jiang, Li; Wang, Guan; Yang, Chunwu; Liu, Bao; Zhang, Zhian
Abstract : Core Ideas: Different tissues displayed different N‐metabolic responses to drought condition. Drought stress enhanced N uptake and assimilation in maize roots. AMT1;1b, AMT1;3, NRT1;2 and NRT2;5 play important roles in maize drought tolerance. Nitrogen metabolism has important roles in plant drought tolerance, and higher N uptake can enhance plant drought tolerance. The aim of this study was to investigate the role of N metabolism regulation in maize drought tolerance. We measured the expression of genes known to be involved in N uptake and assimilation, together with various photosynthetic parameters, and nutrient content, in different tissues from maize plants exposed to water deficit conditions. Different tissues displayed significant differences in their regulation of N metabolism during the adaptation of maize plants to drought stress. The impact of drought on ammonium (NH4 + ) assimilation was much greater in old and mature leaves than in younger leaves. Correspondingly, drought had a smaller effect on photosynthesis in young leaves than in old and mature leaves, suggesting that the disruption of NH4 + assimilation in the latter may be attributable to a greater reduction in photosynthesis. In roots, we found that drought stress dramatically enhanced the expression levels of nearly all genes involved in N uptake and assimilation, including AMT1;3, AMT1;1b, NRT1;2 and NRT2;5, NR, GS2, and GS1;2 . We suggest that increasing the expression of AMT1;1b, AMT1;3, NRT1;2, and NRT2;5 in maize roots under drought condition will increase N uptake and promote rapid accumulation of amino acids. The data revealed that AMT1;1b, AMT1;3, NRT1;2, and NRT2;5 may play important roles in drought tolerance of maize.